ISLAM NUSANTARA - Mujamil Qomar (IAIN Tulungagung, 2019)
This article discusses an Indonesian interpretation of Islam, focusing on the popular concept of Islam Nusantara, the archipelagic Islam. It delves into the account what is Islam Nusantara and the underlying characteristic of the concept. As this article argues, Islam Nusantara reserves as a particular Islamic thought and method. Islam Nusantara is indeed an Indonesian interpretation of Islam that emphasizes on Islam as a cultural phenomenon thus inviting the understanding of religion through a cultural approach. This cultural approach demands pluralities and wasathiyah (moderation) as a main reference for understanding religion. To do so, Islam Nusantara begs inclusive, tolerance and friendly Islamic interpretation and respects differences in terms of cultures and religions. It takes its roots at the Islamic principles of tasamuh, tawazun and i’tidal. Historically speaking, the Javanese nine saints, the Walisongo, is a paradigmatic example in the early Islamic proselytization as translating Islam through cultural fields.